Ultrasound-Induced Blood-Brain-Barrier Opening Enhances Anticancer Efficacy in the Treatment of Glioblastoma: Current Status and Future Prospects. (3rd November 2019) - Deng, Zhiting; Sheng, Zonghai; Yan, Fei
Abstract : Glioblastoma multiforme (GBM) diffusely infiltrates normal brain tissue. The presence of the blood-brain barrier (BBB) poses difficulties for targeted delivery of currently available antitumor drugs. Novel brain drug delivery strategies are far from satisfactory for glioma treatment. Recently, focused ultrasound (FUS) combined with microbubbles presents a transient, reversible, and noninvasive approach for local induction of BBB opening. This strategy demonstrated its potential to increase local concentrations of both diagnostic and therapeutic agents in glioma therapy. Current status and related physic mechanisms of this drug delivery technique are discussed in this review. Delivery efficiency enhancement in many preclinical glioma models was obtained by FUS-BBB opening combined with various nanoparticles. And, the clinical translational status of FUS-BBB will be discussed.